The Pragmatics of AIN’T within Academic and Social Context - Jumanto Jumanto; Rahmanti Asmarani; Sarif Syamsu Rizal; Haryati Sulistyorini (Register Journal, 2022)
This paper has explored the form, the meaning, and the function of the contraction AIN’T, with the corpus data retrieved from English-affiliated URLs or Websites (web-data), through interpretive techniques and a coding analysis. The utterance AIN’T belongs to non-standard or informal English, which represents or is derived from the forms AM NOT, IS NOT, ARE NOT, HAS NOT, HAVE NOT, DO NOT, DOES NOT, DID NOT, and the others. The meaning of AIN’T implies different aspects, i.e. informality, topic area, low social class, emphasis, and content. The utterance AIN’T is part of close language, or is used for close people for friendship or camaraderie. AIN’T belongs to informal utterances, as it is incomplete, shorter, cut-down (or contracted) from other forms. The utterance AIN’T should be taught academically in classrooms or other teaching and learning encounters as informal language with its various derived constructions, and students or learners should be made aware that AIN’T is part of close language which is used to close people for friendship or camaraderie within interpersonal or social context. Use of AIN’T to not close people or superiors or others in a formal situation may lead to a rude situation, and a probable disharmony entails.        Keywords: pragmatics; politeness; camaraderie; informal English; AIN’T.